STRATEGI INDONESIA MENINGKATKAN EKSPOR BIJI KAKAO KE CHINA TAHUN 2018-2022 - Nisya, Khoirun; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Cocoa is one of Indonesia's leading export commodities and plays a vital role in the national economy. However, cocoa bean exports to China fluctuated between 2018 and 2022, necessitating strategies to improve performance. This study aims to analyze Indonesia's strategy for increasing cocoa bean exports to China. The research method used was descriptive qualitative, using secondary data from Statistics Indonesia (BPS), government publications, and academic literature. The analysis was conducted using a liberal perspective and Michael Porter's theory of competitive advantage. The results indicate that the strategies implemented include improving cocoa quality and production, strengthening downstream industries, promoting trade, and bilateral cooperation with China. Synergy between the government, industry players, and farmers is key to increasing the competitiveness of Indonesian cocoa in the global market. Keywords: Export, Cocoa, China, Strategy, Indonesia